Capacity choices and price competition in experimental markets - Vital Anderhub; Werner Güth; Ulrich Kamecke; Hans-Theo Normann (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
In the heterogeneous experimental oligopoly markets of this paper, sellers first choose capacities and then prices. In equilibrium, capacities should correspond to the Cournot prediction. In the experimental data, given capacities, observed price setting behavior is in general consistent with the theory. Capacities converge above the Cournot level. Sellers rarely manage to cooperate.
urn:nbn:de:kobv:11-10048702
Keywords: 330